Beekeeping in the Mediterranean: a medibees survey on practices, trends and challenges - Mangion, Marion Zammit (2022)
MEDIBEES is a PRIMA funded project that aims to identify honeybee colonies and subspecies that are most resilient to climate change and common pathogens throughout the Mediterranean region. Honeybees are critical to sustainable agricultural systems and the project aims to contribute to sustainability in the context of the increased desertification of the region due to climate change. As part of this project an intensive investigation of beekeeping was carried out within the consortium, with the objectives of 1) understanding the main practices in place, 2) identifying trends and challenges faced by beekeepers. This would help guide the consortium in framing research questions that are rooted in the requirements of the stakeholders. A questionnaire was therefore developed and circulated among beekeepers from Algeria, Egypt, Italy, Jordan, Lebanon, Malta, Portugal, Spain and Turkey in late June 2021. To date, over 1300 detailed responses have been collected. This study has yielded an important first profile of the nature of the apicultural industry for many of these participating countries. In this presentation, a description of the socio-demographics and the diverse management practice in place among beekeepers across the Mediterranean will be presented. In addition, important first-time data on the distribution of hives, the main sources of losses including current biotic and abiotic threats, the characteristics and ecological trends of both native and introduced honey bee subspecies in the different geographical regions will be described as experienced by the major stakeholders ie beekeepers. Finally, notably and overwhelmingly, beekeepers from the Mediterranean region list changes in weather patterns as the major factor affecting colony losses and profitability. This was followed closely by indiscriminant use of agricultural insecticides and urbanisation.